Stages Of Organization of Training of Pedagogical Personnel on Creative Education - Jumayev Axrom Asror o’g’li; Amrullayev Behzod Bobur o’g’li (Periodica Journal, 2022)
The author reveals the relevance of the application of creative education in the system of retraining and professional development of pedagogical personnel, the criteria for assessing pedagogical creativity and the stages of organizing training on creative education
Keywords: stages; criteria; personnel; pedagogical